Perlindungan Hak Ekonomi Pencipta Dan Pemegang Hak Cipta Atas Pemutaran Musik Atau Lagu Di Kafe Dan Restoran - Talahatu, Reylandho Cornelius; Berlianty, Teng; Balik, Agustina (KANJOLI Business Law Review, 2023)
Commercially playing music or songs in cafes and restaurants by these business actors are required to pay royalties as regulated in Government Regulation No. 56 of 2021. However, quite a few business actors are still currently refusing and not paying royalties for certain reasons, This act of not paying royalties of course violates the exclusive rights in the form of economic rights of the creator or copyright holder and causes economic losses for the creator or copyright holder. This research uses a normative juridical research method with the legal materials used, namely primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques were carried out through literature study and analyzed using qualitative methods to answer the problems in this research. The results of this research can be concluded that business actors who play music or songs commercially in cafes and restaurants and do not pay royalties have violated the economic rights of creators and copyright holders. The legal consequences of violations of economic rights, as regulated in Government Regulation No. 56 of 2021 and Law No. 28 of 2014, are that creators or copyright holders can file lawsuits and can be subject to compensation fines or imprisonment for business actors who do not pay royalties. It is necessary to expand the reach of LMKN and improve infrastructure so that it can reach small areas, as well as for creators to be able to immediately register their creations to make it easier for LMKN to manage royalties and avoid Copyright violations and to make it easier to resolve problems related to Copyright.